1997
DOI: 10.1095/biolreprod56.4.938
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of Steroidogenic Enzyme Gene Expression in Ovarian Theca-Interstitial Cells in the Rat: Regulation by a Paracrine Theca-Differentiating Factor Prior to Achieving Luteinizing Hormone Responsiveness1

Abstract: The theca cells (TC) first become identifiable in preantral follicles after the granulosa cells (GC) begin to divide. It remains unknown when the TC first respond to LH and acquire the capacity to produce androgens. The signal initiating TC differentiation is also unknown since pre-theca cells do not contain LH receptors. Since the first wave of follicle development in the rat occurs postnatally, we correlated the function of dispersed ovarian cells from 4-, 5-, 6-, 7-, and 10-day-old rats with the morphologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
38
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 31 publications
5
38
0
1
Order By: Relevance
“…All these cytological features are indicative of steroidogenic ability (17), a conclusion supported by the detection of androstenedione at a high concentration in the supernatant. These differentiation patterns of theca cells are consistent with previous findings showing that their proliferation and differentiation are independent of LH receptors in the early stages, but become LH receptordependent at a later stage (18), and that IGF1 synergistically augments the LH stimulation of androstenedione production (19). The stepwise emergence of several theca cell markers is also consistent with a previous in situ hybridization study that suggested that granulosa-derived factors, Ihh and Dhh, are candidate initiators of early thecal differentiation (13).…”
Section: Differentiation Of Putative Thecal Stem Cells In Vitro and Isupporting
confidence: 91%
“…All these cytological features are indicative of steroidogenic ability (17), a conclusion supported by the detection of androstenedione at a high concentration in the supernatant. These differentiation patterns of theca cells are consistent with previous findings showing that their proliferation and differentiation are independent of LH receptors in the early stages, but become LH receptordependent at a later stage (18), and that IGF1 synergistically augments the LH stimulation of androstenedione production (19). The stepwise emergence of several theca cell markers is also consistent with a previous in situ hybridization study that suggested that granulosa-derived factors, Ihh and Dhh, are candidate initiators of early thecal differentiation (13).…”
Section: Differentiation Of Putative Thecal Stem Cells In Vitro and Isupporting
confidence: 91%
“…It is known that under physiological conditions, preantral follicle growth occurs within a rich milieu of endocrine, paracrine and autocrine factors (Kotsuji & Tominaga 1994, Gelety & Magoffin 1997. As a consequence, it may be hypothesised that the availability of an adequate vascular supply providing adequate levels of endocrine and paracrine signals may play a key role in follicle selection Vasculature during preantral follicle development during preantral follicle growth (Danforth 1995, Hull et al 2003, Roberts et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Four rat models, the postnatal, immature, adult and acyclic aged persistent estrous (PE) rat models, are widely used in the literature [9][10][11][12][13][14][15][16][17][18][19][20][21]. Since follicular development in the rat occurs postnatally [11][12][13], we examined the postnatal rat model to determine the relationships between ovarian cAMP l e v e l , c A M P -P D E a c t i v i t y a n d f o l l i c u l a r development.…”
mentioning
confidence: 99%
“…Since follicular development in the rat occurs postnatally [11][12][13], we examined the postnatal rat model to determine the relationships between ovarian cAMP l e v e l , c A M P -P D E a c t i v i t y a n d f o l l i c u l a r development. The immature rats primed with gonadotropin model offers the synchronous nature o f f o l l i c u l a r d e v e l o p m e n t , o v u l a t i o n a n d luteinization [14][15][16].…”
mentioning
confidence: 99%